Pair interactions in induced charge electrophoresis of conducting cylinders. (September 2015) - Feng, Huicheng; Wong, Teck Neng; Marcos,
Graphical abstract: Highlights: The pair interactions in induced charge electrophoresis are characterized. The induced charge electroosmotic flow around the cylinders is analyzed. The cylinder velocities are captured and studied. Abstract: An analytical study on induced charge electrophoresis (ICEP) of two infinite conducting cylinders is presented in this paper. A uniform electric field is applied normal to the axis of the cylinders in two basic ways: perpendicular and parallel to the connecting line of the two cylinders' centers. The electric double layers (EDLs) adjacent to the cylinders are assumed to be much thinner relative to the radius of the cylinders and the distance between the two cylinders. The study reveals that microvortices are generated on the cylinders' surfaces due to the nonlinearity of the induced zeta potentials, which is useful in fluid mixing in micro/nanofluidics. Furthermore, due to the nonuniformity of the surrounding electric field and the asymmetry of the surrounding fluid flow, the cylinders are driven into motion: translating away from each other under the perpendicular applied electric field and migrating towards each other under the parallel applied electric field. The dielectrophoretic (DEP) force due to nonuniform surrounding electric field is much smaller than the ICEP force due to asymmetric surrounding fluid flow, and diminishes to zero significantly as the distance between the two cylinders increases. Thus, the cylinder motion can be accurately described by the ICEP velocities.